HEGEMONI di MEDIA SOSIAL: KASUS AKUN GOSIP INSTAGRAM @LAMBE_TURAH - Christiany Juditha (BPSDMP Kominfo Manado, 2018)
Abstract The latest news about the celebrities can not only be obtained from television infotainment only, but also through gossip accounts in social media. One of them in Instagram account @ lambe_turah. This account is very profitable for business because it can be a media promotion of various products. But by revealing the privacy of people without thinking about the implications and reactions of society because it becomes a problem. Until here hegemony (power) as a social media seems to dominate this phenomenon. Therefore, the purpose of this study is to get an overview of the economic, social and political hegemony of social media on the @lambe_turahgossip account. This research method using literature study. The results conclude that the economic strength of @ lambe_turah can be seen from the messages distributed simultaneously, when and where it can be accepted by its followers consisting of various audiences’ class. With the number of millions followers, @lambe_turah enter the line of endorsement programs that generate economic benefits. Political hegemony @ lambe_turah can be seen freely they post any news about the celebrities either the positive or negative. This unlimited power has made @lambe_turah several times having problems with a number of artists especially if the news is negative. While the cultural hegemony in @ lambe_turah is symmetrically illustrated by the many postings that are like and commented on indicate that netizen's attention is very high. @lambe_turah also has a major influence in the formation of public opinion. Keywords: hegemony, social media, gossip account, instagram, lambe_turah